양성 병소로 오진된 혀에 발생한 선양낭성암종: 증례보고 및 문헌 고찰 - 마윤희; 손창모; 유미현; 황대석 (대한구강악안면병리학회지, 45(4), 2021)
Adenoid cystic carcinoma(ACC) is an uncommon tumor of the head and neck. It is one of the most common malignant tumor of the salivary glands. Although ACC has clear pathologic features, it can be diagnosed as a benign lesion in terms of cytological and radiologic aspects. In this paper, we report a rare case of ACCACC on tongue that is diagnosed as ACC but appears as a benign lesion in cytological and radiologic views. KCI Citation Count: 0